Beveridge Report (letter) - Beveridge, William Henry Beveridge, Baron, 1879-1963. Social insurance and allied services
1943-01 1943 1940s 14 pages : illustrations PICTORIAL CHARTS D W TYLER 76 Halford Street, Leicester. Leicester 59651. 24th February, 1943. The Organiser, London Omnibus Section, Transport and General Workers' Union, Transport House, Smith Square, S.W.1. Dear Sir, In view of the fact that a number of organisations have purchased sets of the enclosed charts dealing with the Beveridge Report in bulk, it occurred to us that your organisation might also find them useful. It can be used in a variety of ways - for display on factory notice boards, in canteens, at meetings, and may also be reproduced in journals (by arrangement with us). The cost of bulk supplies is as follows: Charts - without notes. Charts - with notes. 100 sets............... £3 15s. £4 10s. 500 sets............... £8 5s. £11 0s. 1000 sets............... £13 17s. 6d. £20 10s. As we are unable, by reason of the paper order, to circularise, perhaps you will be kind enough to bring this to the attention of your district organisers. We are enclosing a specimen. Yours truly, JANE CONWAY. JC/MEG Enc. 126/TG/377/1/1/153